Madigan's Luck - Dugan, Bill (New York HarperTorch, 2003)
Rancher Dave Madigan must face cattle rustlers and violent townsfolk while trying to deliever a heard of horses.
Keywords: Cattle drives -- Western stories -- Cattle stealing